Mentality, Systems, and Networking (MSN) Model in Semarang Smart City - Herawati, Augustin Rina; Setianingsih, Endang Larasati; Saputra, Feri Lintang (KnE Social Sciences, 2022)
The fourth modern upheaval period (Industry 4.0) is an opportunity for local governments to carefully develop administrations for the general public. The presence of Semarang Smart City is intended to provide convenience and efficiency for the general public and Regional Government in obtaining a range of data about Semarang City. This review aimed to gain an overview of Semarang Smart City using the mindset, frameworks, and systems administration (MSN) model. This research examined the Semarang Regional Government’s methodology of mindset, disposition, conduct, and obligation, which has a particular focus on the Semarang Smart City and the RPJMD Kota Semarang. The RPJMD contained pointers that were upheld by the city’s execution. The results of the review from the frameworks approach indicated that there was support from the Semarang City Government (Pemkot) to break the old organization’s way of working. The findings from the attitude frameworks and systems administration approach demonstrated the unification of the idea of manageability, availability, inventiveness, and social incorporation with the 6 Smart (6s): smart administration, smart marking, smart economy, smart living, smart society, and smart climate, to become the 10 main programs in the RPJMD of Semarang City in 2016-2021. Keywords: model mentality, systems, networking, Semarang Smart City